Lie point symmetries of difference equations for the nonlinear sine-Gordon equation - Yildirim, Ozgur; Caglak, Sumeyra (IOP Publishing Ltd, 2019)
A procedure for obtaining the Lie point symmetries of a difference scheme for a nonlinear sine-Gordan equation is presented. The invariant discretization of the first order of accuracy difference scheme for the equation is concerned. The symmetry transformations act both on the difference scheme and lattices, and leave the solution set of the difference scheme invariant.
Keywords: Lie symmetry analysis; difference equations; finite difference schemes; Lie point symmetries of difference equations; partial difference equations; SIMILARITY REDUCTIONS; CONSERVATION-LAWS; NONLOCAL SYMMETRY; Physics